PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN LINGKUNGAN (Studi Empiris pada Perusahaan Manufaktur dan Tambang yang Terdaftar pada Bursa Efek Indonesia (BEI) dan Termasuk dalam PROPER Tahun 2009-2011) - Agny Gallus Pratama; Rahardja Rahardja (Diponegoro Journal of Accounting, 2013)
The research was conducted on mining and manufacturing companies to determine the effect of GCG (Good Corporate Governance) that was proxied by (the proportion of independent board, board size, number of board meetings, and the size of the audit committee) and the environmental perfomance against corporate environmental disclosure. Issuance of PP No. 47 Tahun 2012 tentang  "TanggungJawabSosialdanLingkungan" which is the implementing regulations of UU No. 40 Tahun 2007 on "Perseroan Terbatas" Bab V, pasal 74 makes the company must take responsibility for its activities in the social and environmental fields and must be contained in the annual report company. Long period of publication time of PP (5 years) become a question whether the company conducts environmental disclosure eventhough still voluntary. The factors that make a company willing to express their environment disclosure is good corporate governance (GCG) and environmental performance. In the GCG, the principle of accountability, responsibility, and transparability of a company become a reason for company todoenvironemtal disclosure. Beside that, the company's environmental performance is also good reason whether the company will do environmental disclosure. To facilitate assessing how well the quality of environmental disclosure, standard of Global Reporting Index (GRI) 3.1 that was commonly used by companies in Indonesia was used.The population of this study is manufacturing and miningl companies listed in Indonesian Stock Exchange (IDX) and including PROPER in 2009-2011.The total study observations was 85. Sampling technique using purposive sampling method.Techniques of data analysis done by hypothesis testing using multiple linear regression method.Results of this study showed that the proportion of independent board, board size,  and the size of the audit committee no significant effect on environmental disclosure. Meanwhile,there are significant effect on the environmental performance andboard meetings to environmental disclosure.